The influence of social information on norms of cooperation - Eymess, Tillmann (2021)
The provision of information on the behavior and attitudes of others is an effective tool to induce behavioral change. This dissertation studies the effect of such social information interventions in an explicitly social context: cooperative behavior in a social dilemma. It shows under which conditions social norms may become policy tools and establishes that social information not only works with individual actors but also when decisions are made by teams.
Keywords: Hochschulschrift